Metal‐Free Visible‐Light Promoted Radical Cyclization to Access Perfluoroalkyl‐Substituted Benzimidazo[2,1‐a]isoquinolin‐6(5H)‐ones and Indolo[2,1‐a]isoquinolin‐6(5H)‐ones - Zeng, Fan‐Lin; Sun, Kai; Chen, Xiao‐Lan; Yuan, Xiao‐Ya; He, Shuai‐Qi; Liu, Yan; Peng, Yu‐Yu; Qu, Ling‐Bo; Lv, Qi‐Yan; Yu, Bing (Advanced synthesis & catalysis, 2019)
A metal‐free visible‐light‐induced cyclization procedure was developed for the rapid synthesis of perfluoroalkyl‐substituted benzimidazo[2,1‐a]isoquinolin‐6(5H)‐ones and perfluoroalkyl‐substituted indolo[2,1‐a]isoquinolin‐6(5H)‐ones under mild reaction conditions. In this procedure, the formation of electron‐donor‐acceptor (EDA) complex is critical for the visible‐light promoted process to avoid the utilization of external photocatalysts.